(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Zelinskiy S. S. The computer mathematics systems as a tool of formation of the future engineers’ competence in simulation. The article deals with the computer mathematics systems (e. g., Maple) as a tool of formation of the future engineers’ competence in simulation. The concept of computer mathematics system is considered in detail and characteristics of the concept are determined. The possibilities of computer mathematics in the process of future engineers training are given. The practical aspects of the computer mathematics system application are examined.